Rancang Bangun Sistem Informasi Penjadwalan Mata Pelajaran dengan Metode Waterfall - Pratiwi, Indah; Anardani, Sri; Putera, Andi Rahman (JDMIS: Journal of Data Mining and Information Systems, 2023)
Advances in technology that continue to develop make things easier. One application of information technology in the field of education is the existence of a subject scheduling information system. However, until now, the scheduling system at MTsN 03 Madiun still uses the manual method by the curriculum staff. Previously, a joint task distribution meeting was held with the teachers, which then the curriculum staff would confirm the schedule with the instructor, then the admin would supervise one by one the schedules of the teachers who were still empty. Then the schedule needs to be confirmed back to the students. The result of these conditions has an impact on the lack of timely publication of subject schedules which reduces the effectiveness of the learning system. It is not uncommon for errors to occur in scheduling, such as the large number of teaching hours on an inappropriate schedule or subject schedules that clash with other subjects. The schedule that has been made must guarantee that there will be no conflicting schedules, both in hours and instructors. In addition, it takes a long time to make a schedule because the scheduling department needs to adjust the availability of space and teachers. Therefore we need a subject scheduling system that can simplify and minimize errors that occur when preparing schedules. In this study, the method used when collecting data was the observation method, interview method and literature study. In addition, the software development method used was the waterfall method. This system was designed and built using MySQL and PHP as database storage. This subject scheduling system can facilitate curriculum staff and teachers in managing subject schedule information.